The impact of maternal work–family conflict on problem behaviors among preschoolers during the COVID-19 epidemic: a moderated mediation model of maternal anxiety and trait mindfulness - Jin, Xiuzhen; Ahn, Jinkyeong (Frontiers in Psychology, 2023)
The mediating effects of maternal anxiety and moderating effects of trait mindfulness on the relationship between Work-family conflict (WFC) and preschool children's problem behaviors remain unclear during the COVID-19 epidemic. So, this study examined the association between mothers' WFC and preschoolers' problem behaviors and identified the roles of maternal anxiety as a mediator and trait mindfulness as a moderator during the COVID-19 epidemic.In this cross-sectional study, a sample of 1068 Chinese preschoolers and their mothers from coastal cities in southern China were investigated. Data were collected using demographic questionnaires, Carlson's WFC scale, Ma's Parenting Anxiety Scale, Goodman's SDQ Scale, and Brown and Ryan's Trait Mindfulness Scale, and were analyzed using SPSS 26.0 and Process 3.3.Results: WFC had a positive and direct association with problem behaviors in preschoolers (β = 0.118, t =3.880, p < 0.001). WFC also had a positive and direct association with maternal anxiety (β = 0.480, t = 18.034, p <0.001). Maternal anxiety had a positive and direct association with preschoolers' problem behaviors (β = 0.415, t = 13.584, p < 0.001). The mediating effect value of maternal anxiety between WFC and preschoolers' problem behaviors was 0.199, and the moderating effect value of trait mindfulness between maternal anxiety and preschoolers' problem behaviors was -0.078.WFC was positively associated with preschoolers' problem behaviors, and maternal anxiety was a mediator of this association. So, WFC could cause maternal anxiety and lead to more problematic behaviors in children. Besides, maternal anxiety was positively associated with preschoolers' problem behaviors, and trait mindfulness was a moderator of this association.